Histopathological Changes of the Liver in Male White Rats (Rattus Norvegicus) Exposed to Conventional and Herbal Cigarette Smoke - Nussa, Olan Rahayu puji astuti; Kurnianto, Ady; Sigit, Miarsono (Jurnal Medika Veterinaria, 2024)
This research aimed to determine the condition of hepatocyte cells or liver tissue in the liver organ of male white rats exposed to conventional cigarette smoke and herbal cigarette smoke. The samples consisted of 24 white rats with 3 treatments, P1 as a the negative control consisted of 8 white rats without exposure to cigarette smoke, P2 as the group exposed to conventional cigarette smoke, P3 as the group of white rats exposed to herbal cigarette smoke. The study was conducted for 21 days. On day 22, the rats were euthanatized and necropsied, and part of the liver organ was collected. The liver was put into 10% BNF formalin and prepared for histapathology procedure. Microscopic examination was carried out to observe changes in hepatocyte cells, including degeneration or hemorrhage, inflammatory cells infiltration, and necrosis. The results of this study indicated that exposure to both conventional and herbal cigarette smoke causes damage to hepatocyte cells, cellular changes in hepatocytes, vascularization of the liver, including inflammation, necrosis, and degeneration in the hepatic organ